Polemic Of Acceptance And Rejection Of Imam Al-syafei Related To Sadd Al-dhara'i (blocking The Means) As A Source Of Islamic Jurisprudence In Ijtihad Compared To The Acceptance Of Jumhur Fuqaha’ - Mohd Nasir Abd Majid; Ahmad Zaki Salleh; Mohamad Zaharuddin Zakaria; Irwan Mohd Subri; Latifah Abdul Majid (ResearchTrentz, 2024)
Indexed by Scopus/ERA